(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
An experiment was carried to estimate heterotic performances of newly developed test hybrids utilizing CMS system during Rabi 2011 using RCBD design. Five known CMS lines and sixteen developed R-lines were crossed through line × tester analysis. Eighty test hybrids were developed. It is very difficult to find a hybrid earlier to BRRI dhan28 as life cycle of 140 days. Heterosis for days to first flowering varied from -6.23% to 16.35% with a SD of 4.47 meanwhile heterosis for days to 80% flowering varied from -9.24% to 11.04% with a SD of 4.03. Among eighty crosses seventy two were found positive heterosis for days to first flowering but sixty four crosses were found for days to 80% flowering. RG-BU08-016R crosses with IR58025A (-2.68*) and IR62820A (-3.42**) showed significant negative standard heterosis for days to first flowering. Five crosses of IR58025A showed significant negative heterosis with RG-BU 08-005R (-3.42*), RG-BU 08-006R (-5.28**), RG-BU 08-013R (-4.129**), RG-BU 08-016R (-5.78**), RG-BU 08-018R (-4.06*) for days to 80% flowering. Besides these 4 crosses of IR62820A showed significant negative heterosis with RG-BU 08-007R (-2.32*), RG-BU 08-016R (-6.03*), RG-BU 08-018R (-4.58**) followed by GAN 46A/RG-BU 08-006R (-4.58*), BRRI 1A/RG-BU 08-001R (-2.55**) and BRRI 1A/RG-BU 08-006R (-9.24**) resulted significant negative heterosis for days to 80% flowering. Positive heterosis were recorded for IR58025A with RG-BU 08-007R (26.97**), RG-BU 08-0046R (8.77**) and RG-BU 08-105R (14.44**) for PER and RG-BU 08-018R (42.46**), RG-BU 08-046R (112.30**), RG-BU 08-057R (27.46*) for SER. While two R-lines, RG-BU 08-013R (25.41**) and RG-BU 08-057R (7.21*) were found having significant positive heterosis for panicle exertion rate crosses with IR62820A but RG-BU 08-025R (52.82**), RG-BU 08-057R (122.66**) and RG-BU 08-063R (37.38**) were found having significant positive heterosis for SER. IR62820A/RG-BU08-057R showed significant positive heterosis for both panicle and stigma exertion rate. GAN46A/RG-BU 08-063R (5.65* & 133.02**) was recorded showing significant positive heterosis for both panicle and stigma exertion rate where. But the crosses of IR68888A was not shown exhibiting a great contribution for panicle and stigma exertion rate except RG-BU08-018R (25.94**). Meanwhile the crosses of BRRI1A was recorded having significant positive heterosis for PER with RG-BU08-005R (13.41**), RG-BU08-007R (5.65*) and RG-BU08-097R (25.94**) as well as RG-BU08-007R (133.02**), RG-BU08-013R (48.19**) and RG-BU08-038R (29.21*) were recorded having significant positive heterosis for SER.